Economic complexity and Information Society paradigms: a hybrid contribution to explain economic growth - Jurado-González, Javier; Gómez-Barroso, José Luis (Technological and Economic Development of Economy, 2022)
In the last decades, the Information Society (IS) paradigm has brought together various research lines related to the diffusion and adoption of Information and Communication Technologies (ICTs) and their contribution to economic, social and human development. On the other hand, other research lines have recently explored the phenomenon of Economic Complexity (EC), providing new metrics to quantify this decisive factor for the prediction of economic growth and other human relevant variables. This article explores these two trends with the construction of two composite indexes. Then, it evaluates their explanatory power to predict economic growth, first separately, and afterwards together. The results show they can predict economic growth and improve their predictive capacity by working combined. In the conclusions, some difficulties and challenges for the development of these metrics are analyzed.